Research methods : concepts and connections - Passer, Michael W. (New York : Worth Publishers, 2014)
Offers students clear and compelling explanations and examples drawn from cutting-edge research from across the subfields of psychology. Readers come away with an unparalleled understanding of behavioral research practice in today's world and how those skills apply to everyday life.
Includes bibliographical references and indexes.
Keywords: Psychology -- Research -- Methodology; Social sciences -- Research -- Methodology; Psychology -- Research -- Methodology; Social sciences -- Research -- Methodology